2010
DOI: 10.1073/pnas.1000848107
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of UGUA recognition by the Nudix protein CFI m 25 and implications for a regulatory role in mRNA 3′ processing

Abstract: Human Cleavage Factor Im (CFI m ) is an essential component of the pre-mRNA 3′ processing complex that functions in the regulation of poly(A) site selection through the recognition of UGUA sequences upstream of the poly(A) site. Although the highly conserved 25 kDa subunit (CFI m 25) of the CFI m complex possesses a characteristic α/β/α Nudix fold, CFI m 25 has no detectable hydrolase activity. Here we report the crystal structures of the human CFI m 25 homodimer in complex with UGUAAA and UUGUAU RNA sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
146
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 48 publications
13
146
0
Order By: Relevance
“…As the molecular weights of CF I m 25 and CF I m 68RRM are 24 and 10 kDa, respectively, this result suggests that the CF I m 25-CF I m 68RRM complex exists as a heterotetramer in solution. The heterotetrameric state is also consistent with previous reports that two subunits of CF I m form a heterotetramer in solution [17]. Outlier (%) 0.1 …”
Section: Overall Structure Of the Cf I M 25-cf I M 68rrm Complexsupporting
confidence: 80%
See 4 more Smart Citations
“…As the molecular weights of CF I m 25 and CF I m 68RRM are 24 and 10 kDa, respectively, this result suggests that the CF I m 25-CF I m 68RRM complex exists as a heterotetramer in solution. The heterotetrameric state is also consistent with previous reports that two subunits of CF I m form a heterotetramer in solution [17]. Outlier (%) 0.1 …”
Section: Overall Structure Of the Cf I M 25-cf I M 68rrm Complexsupporting
confidence: 80%
“…Recently, CF I m has been shown to be a heterotetramer in solution [17]. Our structure confirms that CF I m 25 [17] observed that the CF I m 25 dimer bound RNA containing two separated UGUAA elements with 100-fold higher affinity than RNA containing only one UGUAA element.…”
Section: Cf I M 25 Dimerization Is Crucial For Uguaa Recognition and supporting
confidence: 75%
See 3 more Smart Citations